Active ignoring in early visual cortex - Payne, Helen; Allen, Harriet A. (MIT, 2011)
Selective attention is critical for controlling the input to mental processes. Attentional mechanisms act not only to select relevant stimuli but also to exclude irrelevant stimuli. There is evidence that we can actively ignore irrelevant information. We measured neural activity relating to successfully ignoring distracters (using preview search) and found increases in both the precuneus and primary visual cortex during preparation to ignore distracters. We also found reductions in activity in fronto-parietal regions while previewing distracters and a reduction in activity in early visual cortex during search when a subset of items was successfully excluded from search, both associated with precuneus activity. These results are consistent with the proposal that actively excluding distractions has two components: an initial stage where distracters are encoded, and a subsequent stage where further processing of these items is inhibited. Our findings suggest that it is the precuneus that controls this process and can modulate activity in visual cortex as early as V1.